L05 SW Thames Regional Genetics Service – Audit of the HD Service. (17th September 2014) - Lahiri, N; Eddy, CM; Anjum, U; McEntagart, M
Abstract : Background: The South West Thames Regional Genetics Service was established at St. George's Hospital in 1986 and has expanded greatly over the last 25 years. The Regional Genetics Service serves a population of over 3.1 million. The HD service has been provided through monthly specialist clinics at St. George's and ad-hoc in a number of local district general hospitals across the region and historically has comprised of consultant clinical geneticists and genetic counsellors. Aims: The are several models for an HD specialist service and the structure of sevices varies nationwide. The aim of this audit was to collect information on the historic practice at St. George's evaluating diagnostic and predictive testing against existing guidelines whilst also collecting information of the structure of the service and user satisfaction using a parallel audit of notes and a patient survey. Methods: A patient survey was sent to 167 patients with a diagnostic code of Huntington's disease either seen by the department or tested by the laboratory between the years 2009-2011. A parallel notes audit of all the patients who returned surveys was carried out. Results: Despite NHS tracing all patients, only 21% of surveys were returned. Of those who responded, the vast majority were patients who had attended for predictive genetic counselling. 53% were gene negative, 19% had not had genetic testing and 30% were gene positive. 89% rated the support they recieved as good but only 75% felt their psychological needs were adequately met and over 50% felt that there were improvements to their experience that could be made. In particular there was a lack of follow-up, family support & research opportunities. Conclusions: The information collected in the course of audit will be used to help shape a more robust HD service and we hope to use a modified version of this patient questionnaire to expand this audit UK-wide. There was a lack of response from symptomatic patients and this group requires further study. The strongest message from patients is that they are asking for emotional support and family follow-up.